Two-stage algorithm for the management of distributed energy resources included in an aggregator's activities - Spínola, João (2021)
The growing number of distributed energy resources in power systems, leads to the appearance of new entities and roles for the existing ones that affect the operation of the network. One of these entities with more relevance, is the aggregator, either independent or represented by public organizations. An aggregator manages small-sizemdistributed energy resources, creating a virtual amount of energy flexibility that can be used by it, to enablem participation in energy markets and capitalize the integration of distributed energy resources. This paperm proposes a two-stage optimization methodology for the operation of an aggregator regarding distributed energy mresources. In a first stage, the network part managed by the aggregator is scheduled, meaning at a macrom perspective, while in the second stage, it is assumed that the distributed energy resources are also scheduled mconsidering their operation. It is assumed that this second stage is enabled due to an aggregator’s communication infrastructure and interconnected management systems.